How false news can spread - Noah Tavlin (SaferInternet4Kids- Ελληνικό Κέντ. Ασφαλ. Διαδικτ., 2015)
: large waist There's a quote usually attributed to the writer Mark Twain that goes A lie can travel halfway around the world while the truth is putting on its shoes. Funny thing about that, there's reason to doubt that Mark Twain ever said this at all, thus ironically proving the point, and today the quote, whoever said it, is truer than ever before. In previous decades, most media with global reach consisted of several major newspapers and networks which had the resources to gather information directly. Outlets like Reuters and the Associated Press that aggregate or re-report stories were relatively rare compared to today. The speed with which information spreads now has created the ideal conditions for a phenomenon known as circular reporting. This is when publication A publishes misinformation, publication B reprints it, and publication A then cites B as the source for the information. It's also considered a form of circular reporting when multiple publications report on the same initial piece of false information, which then appears to another author as having been verified by multiple sources. For instance, the 1998 publication of a single pseudoscientific paper arguing that routine vaccination of children causes autism inspired an entire anti-vaccination movement, despite the fact that the original paper has repeatedly been discredited by the scientific community. Deliberately unvaccinated children are now contracting contagious diseases that had been virtually eradicated in the United States, with some infections proving fatal. In a slightly less dire example, satirical articles that are formatted to resemble real ones can also be picked up by outlets not in on the joke. For example, a joke article in the reputable British Medical Journal entitled Energy Expenditure in Adolescents Playing New Generation Computer Games has been referenced in serious science publications over 400 times. User-generated content such as Wikis are also a common contributor to circular reporting. As more writers come to rely on such pages for quick information, an unverified fact in a Wiki page can make its way into a published article that may later be added as a citation for the very same Wiki information, making it much harder to debunk. Recent advances in communication technology have had immeasurable benefits in breaking down the barriers between information and people. But our desire for quick answers may overpower the desire to be certain of their validity. And when this bias can be multiplied by billions of people around the world nearly instantaneously, more caution is in order. Avoiding sensationalist media, searching for criticisms of suspicious information, and tracing the original source of a report can help slow down a lie, giving the truth more time to put on its shoes.